Pengaruh Labelisasi Halal, BPOM, Dan Citra Merek Terhadap Pembelian Produk Skincare Pada Mahasiswi Ekonomi Syariah 2023 Universitas Sultan Ageng Tirtayasa - Mahyani, Wiwit; Mukhsin, Moh (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The beauty product industry, including skincare, has experienced rapid growth in recent years. In Indonesia, as a country with a majority Muslim population, the need for halal skincare is very high. Students majoring in Sharia Economics at Sultan Ageng Tirtayasa University, with a good understanding of Islamic law, are more selective in choosing skincare products. This study aims to understand the factors that influence purchasing decisions for skincare products for Sharia Economics students at Sultan Ageng Tirtayasa University. The factors studied include halal labeling, BPOM certification, and brand image. This research uses quantitative methods with saturated sample techniques. The results showed that the halal label, BPOM certification, and brand image had a significant effect on purchasing decisions for skincare product